Impact of charge-coupled device size on axial measurement error in digital holographic system - Hao, Yan (2013)
Digital holography (DH) is a 3D measurement technique with a theoretical axial resolution of better than 1-2 nm. However, practically, the axial resolution has been quoted to be in the range 10-20 nm. One possible reason is that the axial measurement error is much larger so that the theoretical axial resolution cannot be achieved. Until now the axial measurement errors of the DH system have not been thoroughly discussed. In this Letter, the impact of CCD chip size on the axial measurement error is investigated through both simulation and experiment. The results show that a larger CCD size reduces the axial measurement error and improves the measurement accuracy of edges.